Абсурдизация действительности в сатирической пьесе Увидеть Солсбери Виктора Шендеровича - Vorontsova, Kristina (Studia Rossica Posnaniensia, 2022)
In 2018, the story of the unsuccessful poisoning of the Skripals by Russian special services shocked the world, and the further appearance of “Petrov” and “Boshirov” in an interview with Margarita Simonyan with completely implausible explanations led to the emergence of many memes and humorous works. The satirical play by Viktor Shenderovich To see Salisbury (2019) can be considered as one of the most significant reactions created by Russian-speaking society to the lies of the state. It is successfully performed abroad and, of course, has no chance of being staged in Russia. The author asks the question: what if everything that Petrov and Boshirov told in a scripted interview on the air of on Russia Today is true, and they are not unsuccessful spies, but a couple of gay lovers who are interested in Gothic cathedrals and the Charter of Liberties? Reflections on their own blurry unstable identity led the characters to an existential crisis in the spirit of the Theatre of the Absurd. This paper analyses how the absurdity of reality in the play serves to create a comic effect. Shenderovich grounds his satire based on direct citation of the precedent text of the interview, known a priori to every Russian-speaking recipient, on the intertexts of the Russian linguistic culture, fills the gaps of perception with paradoxes, and answers the questions asked by the audience after the RT broadcast (Why do the passport numbers differ by one digit? Why do the characters know Simonyan’s personal phone number? etc.).